2015
DOI: 10.1016/j.cherd.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of drag reduction effect by simultaneous addition of surfactant and high molecular polymer into the solvent

Abstract: Clear existence of three drag reduction zones was observed: stable transitional zone, unstable transitional zone and in particular the third turbulent drag reduction zone.The dominant factor which influenced DR in the transitional zone was the addition of CTAB + NaSal. In the third zone, the addition of PEO had decisive influence on the DR intensity. The increase of PEO concentration enhanced DR in this zone.The influence of pipes diameter on the DR was investigated. The increase of pipe diameter caused clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…In addition, the complex mixture formed from the combination of any two or more additives performs better than the individual parties. A similar observation was made in [24,29,30]. This performance was expected because of the successful interaction between the surfactant micelles and polymers chains that formed a viscoelastic polymer-surfactant complex.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In addition, the complex mixture formed from the combination of any two or more additives performs better than the individual parties. A similar observation was made in [24,29,30]. This performance was expected because of the successful interaction between the surfactant micelles and polymers chains that formed a viscoelastic polymer-surfactant complex.…”
Section: Resultssupporting
confidence: 53%
“…Different complex mixtures have been used recently as DRAs in pipelines [24,30,31] and rotating disk apparatus [32][33][34][35]. Mohsenipour et al [24] studied the interaction between an anionic copolymer, which comprises acrylamide and sodium acrylate (referred to as PAM) and cationic surfactant of octadecyltrimethylammonium chloride (OTAC), in pipeline flow.…”
Section: Introductionmentioning
confidence: 99%
“…The present investigations have shown that polymers or surfactants alone as the drag‐reducing agent have certain advantages and disadvantages due to their properties. For instance, polymers can induce the efficient drag reduction at a relatively low concentration, but they are susceptible to thermal or/and mechanical degradation at the intense shear or the high temperature . Such degradation is permanent and irreversible, which leads to lost in the drag reduction function.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Matras and Kopiczak, the drag reduction phenomenon by the combined control of polymers and surfactants is still a relatively new and poorly recognized academic issue. Up till now, only a small number of scholars carried out the related studies.…”
Section: Introductionmentioning
confidence: 99%
“…The use of diverse polymers such as DRAs has been reported previously (Abubakar et al 2014;AlSarkhi 2012;Matras and Kopiczak 2015;Edomwonyi-Outu, Chinaud and Angeli 2015;Hong et al 2015;Iaccarino et al 2010;Resende et al 2011) and surfactants (Drzazga et al 2013;Li et al 2008;Różański 2011;Yu and Kawaguchi 2006;Tuan Mizunuma 2013;Qi et al 2011) depending upon the polarities and different behaviors in a turbulent flow (Tarn and Pamme 2014), while the impact of other colloidal suspensions, such as nanofluids, in reducing the pressure drop has not been widely studied. The dispersion quality of the nanoparticles in the base fluid and the stability of the suspension play a crucial role in most applications of practical interest (Rivet et al 2011;Xie et al 2003;Choi et al 2007;Ganguly et al 2009).…”
Section: Introductionmentioning
confidence: 99%